Comparative Analysis of the Effect of Needle-Based Spinneret/Collector Combinations on Morphological Properties of PVA Electrospun Mats - Hayriye Hale Aygün (Nanomaterials and Nanotechnology)
Electrospinning is a promising technique for enabling the manipulation of the structural properties of nano- or microfibrous mats by altering electrospinning parameters. In this paper, it is aimed to examine the morphological variations of electrospun mats fabricated by combinations of different collector types and feeding units. In horizontal electrospinning setup, PVA polymer solutions are transformed to polymer jets by the help of needle-based feedings with single- and multinozzles. Electrospun fibers are deposited on four different collector types with identical collector-nozzle distance, feeding rate, applied voltage, and environmental conditions. It is concluded that the coarsest nanofibers are fabricated by multineedle/disc collector combination and the disc collector causes flat nanofiber handling with multineedle feeding but not with single needle feeding. On plate collector, thicker electrospun mats are obtained whichever feeding type is used. Average pore sizes on mats are found higher in multineedle feeding, especially with deposition between rods of birdcage collector. Changing the feeding type from multineedle to single needle causes to manufacture of electrospun mats with a narrower surface area and an increase is observed in packing density, basis weight and % porosity but a decrease in pore size and mat thickness with this manipulation. Nanosized but flattened electrospun fibers are handled by multineedle/disc collector and two distinct compositions are incorporated by deposition of nanofibers on birdcage collector.